The World Ovarian Cancer Coalition Every Woman Study: identifying challenges and opportunities to improve survival and quality of life. Issue 2 (February 2021) - Reid, Frances; Bhatla, Neerja; Oza, Amit M; Blank, Stephanie V; Cohen, Robin; Adams, Tracey; Benites, Amanda; Gardiner, Diane; Gregory, Sylvia; Suzuki, Makiko; Jones, Annwen
ABSTRACT : Introduction : With the global incidence of ovarian cancer set to rise by 55% to 371 000 per year by 2035, current 5‐year survival rates below 50%, and 15% of women with ovarian cancer dying within 2 months of diagnosis, urgent action is required to improve survival and quality of life. Objective : To deal with the evidence gap relating to the experience of women with the disease around the globe and identify opportunities to drive progress. Methods : The study included a review of global trends in incidence, mortality, and survival (October 2017); qualitative interviews with women and clinicians in 16 countries (December 2017); and an online survey for women available in 15 different languages (open for 2 months, March to early May 2018). Women were eligible to participate if they had been diagnosed in the previous 5 years and were proficient in one of the 15 languages offered. Results : A total of 1531 women from 44 countries took part in the analysis. On average, 69.1% of women were not aware of ovarian cancer before their own diagnosis, varying from 50.9% (Hungary) to 86.4% (Brazil). A total of 78.3% of symptomatic women sought medical help, varying from 62.8% (Japan) to 87.7% (UK). Fewer than half of the women visited a doctor within 1 month (46.3%) of experiencing symptoms, varying from 38.5% (USA) to 77.3% (Germany), and a quarter of women waited 3 months or more. On average, 43.2% of women were diagnosed within 1 month of visiting a doctor, ranging from 30% (UK) to 62.3% (Italy). The average estimated time from experiencing symptoms to diagnosis was 31 weeks, but this ranged from 21.3 (Germany) to 39.7 (Brazil). Rates of post‐diagnosis genetic testing ranged from 5.0% (Japan) to 79.1% (USA). Clinicians indicated that access to specialist treatment in high‐volume centers varies greatly by country and region. Conclusion : The findings of this study identify some of the major challenges and opportunities to improve the time to diagnosis and management of women with ovarian cancer. These problems vary widely by country, and reducing the variability is an important first step towards improving outcomes for women with ovarian cancer.